Class Size and Teacher Work: Research Provided to the BCTF in their Struggle to Negotiate Teacher Working Conditions - Laitsch, Daniel; Nguyen, Hien; Younghusband, Christine Ho (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2021)
This paper presents an update of a 2010-literature review on class size research completed as background in preparation of an affidavit on class size provided by the lead author in the case of British Columbia Teachers’ Federation v. British Columbia, argued before the Supreme Court of British Columbia in 2010, appealed ultimately to the Supreme Court of Canada and ruled on November 10, 2016.  We find that smaller classes can improve teacher-student interactions and individualized instruction, decreasing time spent on discipline issues, leading to better student behaviour, attitude, and efforts. Smaller classes generally have greater advantages for younger students, and effects are more observable in class sizes of less than 20. Small classes may shrink achievement gaps, decrease dropout rates, and increase high school graduation rates, and appear to enhance academic outcomes, particularly for marginalized groups. Researchers have detected class size effects many years later. Small classes have been found to boost teachers’ morale and job satisfaction. While some studies have found effects at the secondary and post-secondary level, results are generally inconclusive at this level. Finally, some researchers have argued that class size reductions are an inefficient use of funds which might be better spent elsewhere in the system. The paper concludes with a brief reflection on the process of providing this research for Supreme Court case.